2022
DOI: 10.18388/abp.2020_6271
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cardiovascular diseases in kidney transplant recipients and its relationship with asymmetric dimethylarginine, fibroblast growth factor-23 and multiple inflammatory markers

Abstract: Introduction and aim: Asymmetric dimethylarginine (ADMA) is an endogenous inhibitor of endothelial nitric oxide synthase, a marker of endothelial damage and progression of atherosclerosis. Research confirms the association of ADMA with an increased risk of cardiac complications and an increased risk of death, graft loss among kidney transplant recipients (KTRs). The aim of our study was to establish the significance of ADMA and FGF-23 as biomarkers of cardiovascular risk as well as predictors of graft failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(51 reference statements)
0
1
0
Order By: Relevance
“… 12 Serum CRP levels are significantly elevated in patients with CKD, 13 and gradually increasing CRP levels over time are associated with increased risk of hospitalization in patients with CKD, 14 and hs‐CRP is associated with risk of cardiovascular events and mortality in patients with CKD. 15 In addition, studies have shown that FGF‐23 levels are positively correlated with hs‐CRP, 16 Serum 25‐hydroxyvitamin D is negatively correlated with CRP in patients with vitamin D deficiency, 17 and hs‐CRP levels in the severe SHPT group are higher than those in the mild SHPT group. 18 In summary, CKD, the increase of FGF‐23, and vitamin D deficiency are all associated with the occurrence of SHPT, and they are all associated with CRP.…”
Section: Introductionmentioning
confidence: 99%
“… 12 Serum CRP levels are significantly elevated in patients with CKD, 13 and gradually increasing CRP levels over time are associated with increased risk of hospitalization in patients with CKD, 14 and hs‐CRP is associated with risk of cardiovascular events and mortality in patients with CKD. 15 In addition, studies have shown that FGF‐23 levels are positively correlated with hs‐CRP, 16 Serum 25‐hydroxyvitamin D is negatively correlated with CRP in patients with vitamin D deficiency, 17 and hs‐CRP levels in the severe SHPT group are higher than those in the mild SHPT group. 18 In summary, CKD, the increase of FGF‐23, and vitamin D deficiency are all associated with the occurrence of SHPT, and they are all associated with CRP.…”
Section: Introductionmentioning
confidence: 99%